CHARACTERISTICS OF COW'S MILK KEFIR MASK WITH THE ADDITION OF CENDANA FRANGIPANI FLOWER FLOUR (Plumeria alba) AFTER INCUBATION - E., Mulfindarochma; Lindawati, S. A.; Miwada, I N. S. (Jurnal Peternakan Tropika, 2022)
Kefir is a fermented milk product that is used as a basic ingredient for masks for facial skin care. This study aimed to determine the characteristics of cow's milk kefir mask with the addition of cendana frangipani  flower flour ( Plumeria alba ). This research was conducted at the Laboratory of Animal Products Technology and Microbiology, Faculty of Animal Husbandry, Udayana University from February to April 2021. The experimental design used was a completely randomized design (CRD) with four treatments and four replications. The four treatments were: kefir masks without the addition of cendana frangipani flower flour (P0), kefir masks with the addition of 2% cendana frangipani flower flour (P1), kefir masks with the addition of 4% cendana frangipani flour flour (P2), kefir masks with the addition of 6% cendana frangipani flower flour (P3). The results showed that the antimicrobial activity against  Staphylococcus aureus obtained an inhibition zone of 9.38 – 11.07 mm. The range of pH values ??in all treatments ranged from 4.66 - 4.89, while the stickiness showed that the higher the concentration of addition of cendana frangipani flower flour, the higher the stickiness (10.40 - 17.73) minutes and the panelists' preference for (color, aroma, texture) showed that the results were not significantly different (P>0.05) with the criteria leading to preference. Based on the results of this study, it can be concluded that the kefir mask with the addition of  cendana frangipani flower flour has no effect on the antimicrobial activity of Staphylococcus aureus and the organoleptic preference level (color, aroma, texture) but has an effect on the pH value and adhesion with the addition of 2% - 6% cendana frangipani flower flour. Key words: Characteristics, kefir mask, cendana frangipani  flower